PENGARUH KUALITAS LAYANAN DAN SARANA PRASARANA LAB KOMPUTER TERHADAP KEPUASAN MAHASISWA (STUDI PADA MATA KULIAH APLIKASI KOMPUTER MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI UNIVERSITAS BHINNEKA PGRI) - Hana Unnisa (Bhinneka PGRI University); Dr. Imam Sukwatus Suja’i M., Si (STKIP PGRI TULUNGAGUNG, 2022)
AbstractThis study aims to determine: (1) the quality of services and computer lab infrastructure at the University of Bhinneka PGRI, (2) student satisfaction at the University of Bhinneka PGRI, (3) the influence of the quality of services and computer lab infrastructure on student satisfaction at the University of Bhinneka. PGRI. The type of research used in this research is associative research with a quantitative approach method. The research subjects were University of Bhinneka PGRI students totaling 58 people and using the Random Sampling technique. Data collection techniques were carried out through a questionnaire. Data analysis used quantitative descriptive analysis and inferential analysis through multiple linear regression analysis. The results showed that the quality of service in the category is quite good, namely with a percentage of 62.1%, infrastructure facilities are in a fairly good category with a percentage of 69% and student satisfaction is in the category of not good, with a percentage of 41%. The results of inferential statistical analysis showed the value of fcount (36,186) ftable (3,165) at the significance level. Based on these results, it can be concluded that the quality of service and computer lab infrastructure has a significant effect on student satisfaction. Keywords: The Quality of Services, infrastructure facilities, Computer Lab, Satisfaction